ANALISIS PENGENDALIAN PIUTANG TERHADAP RESIKO PIUTANG TAK TERTAGIH PADA CV. TEGUH HARAPAN DI KABUPATEN BERAU (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2017)
Analysis of Accounts Receivable Management against Risk of Doubtful Accounts at CV. Teguh Harapan in Berau District. The purpose of this study is to analyze the control of accounts receivable against the risk of bad debts on the CV. Teguh Harapan in Berau District. The analytical method used is descriptive method that is analyzing data by determining, collecting, clarifying, analyzing and interpreting therefore are able to produce a clear description for controlling the accounts receivable to the risk of bad debt. Based on the results of the analysis can be concluded that CV. Teguh Harapan has established a credit policy in accordance with the prevailing provisions regarding the credit terms, credit standards and billing policies. Teguh Harapan applies 5C (Capacity, Character, Capital, Collateral, Condition). CV policy. Teguh Harapan in controlling the receivables is by estimating the bad debts of 7%. From the method of allowance for doubtful accounts and the determination of uncollectible accounts receivable loss using loss of accounts receivable and age analysis of receivables, it can be seen that the amount of bad debts in Year 2015 amounted to 6.72% of total receivables. Thus, it can be concluded that the control of bad debts for CV. Teguh Harapan was solved.